2018
DOI: 10.3390/app8081311
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Vibration Analysis of Submerged Floating Tunnel System in Wave and Current

Abstract: Featured Application: A simplified theoretical model is proposed for vibration analysis of the coupled Submerged floating tunnel (SFT) tube-cable system under combined vortex-induced and wave forces. Several cases under different working conditions are presented to reveal the dynamic characteristics of the SFT. This approach can be extended to future actual structures to determine structural parameters and avoid strong resonance.Abstract: Submerged floating tunnel (SFT) is an innovative underwater structure fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Xiang and Chao [17] adopted this model to study the vortex-induced vibration of cable under the action of current, which analyzed the influence of water flow velocity, cable inclination angle and tunnel buoyancy ratio on the structure response. Chen et al [18] used this model to study the coupled vibration analysis of submerged floating tunnel in wave and current. Besides, the paper analyzed the influence of water flow velocity, cable inclination and wave period.…”
Section: Introductionmentioning
confidence: 99%
“…Xiang and Chao [17] adopted this model to study the vortex-induced vibration of cable under the action of current, which analyzed the influence of water flow velocity, cable inclination angle and tunnel buoyancy ratio on the structure response. Chen et al [18] used this model to study the coupled vibration analysis of submerged floating tunnel in wave and current. Besides, the paper analyzed the influence of water flow velocity, cable inclination and wave period.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental loads include waves, earthquakes, currents, and tsunamis. Among them, waves tend to be the most important environmental loading if the submergence depth is not sufficiently large [3][4][5][6][7]. For SFT with a large diameter, it was found through hydro-elastic analysis that large static and dynamic mooring tensions were critical issues [7].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the vortex-induced vibration resonance occurred and the axial stress of the structure increased significantly. Chen et al [20] proposed a simplified theoretical model for vibration analysis of the coupled SFT tube-cable system under wave and current.…”
Section: Introductionmentioning
confidence: 99%